PENGARUH PELAYANAN KARYAWAN TERHADAP CITRA PERUSAHAAN INDOMARET DI KOTA BATAM - Reza, Ana; Purwanti, Angel (LPPM Universitas Putera Batam, 2021)
Research objectives: To determine the quality of employee service related to the image of the company Indomaret, and to determine the quality of employee service affects the image of the company. This research method uses a quantitative approach. By spreading 345 respondents with random sampling method. Distribution of questionnaires conducted to consumers who have experienced the services provided by employees. The analysis in this study used the validity test, reliability test, normality test, correlation test, regression test using SPSS. The benefit of this research is that it can provide information about the quality of employee service to the company's image, and can be used as a reference to complement future researchers. The results of the research on the quality of employee service have an effect on company image.